Invitation for a party for Al Lowenstein (1976)
This flyer invites attendees to a July 13, 1976 late-night party at the New York Hilton in support of Al Lowenstein, former congressman and Democratic nominee for Congress (5th District). It features a quotation from Robert F. Kennedy about Lowenstein and lists numerous prominent political leaders, activists, and entertainers as sponsors. The event, held in the Rhinelander Ballroom, includes music and entertainment with a suggested donation of $12.50 per person.